2021
DOI: 10.1038/s41598-021-02581-9
|View full text |Cite
|
Sign up to set email alerts
|

Development of novel robotic platforms for mechanical stress induction, and their effects on plant morphology, elements, and metabolism

Abstract: This research evaluates the effect on herbal crops of mechanical stress induced by two specially developed robotic platforms. The changes in plant morphology, metabolite profiles, and element content are evaluated in a series of three empirical experiments, conducted in greenhouse and CNC growing bed conditions, for the case of basil plant growth. Results show significant changes in morphological features, including shortening of overall stem length by up to 40% and inter-node distances by up to 80%, for plant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 54 publications
(67 reference statements)
0
4
0
Order By: Relevance
“…Several other production style methods have developed that include soft clothes [96], motion vibrators [97], roll-table system [98]. More recently, in a well-devised experimental design, the authors used two different robotic platforms for investigating the potential of automation in a MS study [99,100]. In the first case, a seven-DoF Franka Emika robotic arm, equipped with a stroking end-effector consisting of a row of plastic strings, was placed in a greenhouse setting.…”
Section: Automation Of Ms Treatment For Potential Benefitsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several other production style methods have developed that include soft clothes [96], motion vibrators [97], roll-table system [98]. More recently, in a well-devised experimental design, the authors used two different robotic platforms for investigating the potential of automation in a MS study [99,100]. In the first case, a seven-DoF Franka Emika robotic arm, equipped with a stroking end-effector consisting of a row of plastic strings, was placed in a greenhouse setting.…”
Section: Automation Of Ms Treatment For Potential Benefitsmentioning
confidence: 99%
“…Further, MS treatments resulted in increased DHA (Dehydroascorbic acid) and GABA levels. The authors concluded that increases in these metabolites is linked to build up of ROS and changes in nitrogen metabolism and aminoacid accumulation with mechanical induced abiotic stress [99,100]. In another interesting application, a model automated touch machine was designed for the purpose of studying the effect of touch response in Arabidopsis thaliana [101].…”
Section: Automation Of Ms Treatment For Potential Benefitsmentioning
confidence: 99%
“…Moreover, mechanically-induced stress can increase the content of specialized metabolites and antioxidant capacity of leafy vegetables [13]. It has also been reported [18] that mechanical stimulation can improve the nutritional properties of plants by increasing the absorption of elements and changes in metabolite profile. In addition, mechanical stimulation has been shown to lead to acclimation and tolerance to other stress conditions such as frost, cold, heat, salt, drought, and pathogen attack [19,20].…”
Section: Introductionmentioning
confidence: 97%
“…The studies conducted so far included different types of mechanical stimuli, however they were rarely quantified, making it difficult to compare data from different studies as pointed out by Coutand [65]. In most cases, mechanical stimuli have been quantified as the number of rubbing [22], touching [21], bending [66], and brushing treatments [15], and these studies have focused mainly on the effects on growth, morphological, and developmental changes [18,67]. Unlike these long-term effects, mechanical stimulation triggers numerous physiological and biochemical changes that can be detected in a much shorter time than phenotypic modifications.…”
Section: Introductionmentioning
confidence: 99%